PENGARUH MEDIA LEMBAR BALIK TERHADAP PENGETAHUAN IBU BALITA DALAM PENCEGAHAN STUNTING DI POSYANDU SANDEN KOTA MAGELANG - Sari, Devi Permata; Kurniasih, Dwi Endah; Rusyani, Yelli Yani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Background: Stunting is a condition of growth failure due to malnutrition in the first thousand days of a child's life. One of the factors that cause stunting is the lack of maternal knowledge. One method to increase maternal knowledge is counseling using flipchart media. Objective: To determine the effect of counseling with flipchart media on the knowledge the mothers in preventing stunting at Posyandu Sanden Magelang City. Research Methods: The method used in this study is quantitative with a Pre-experimental approach. The samples of this study are 30 respondents from the total population of 40 mothers of toddlers, the sampling technique used purposive sampling. The instruments used were questionnaires and flipchart media. In this study Univariate data analysis use frequency distribution and bivariate use Wilcoxon test. Research Results: There is an effect of flipchart media on the knowledge of mothers in preventing stunting with a p-value of 0.000 (p <0.05). The knowledge of the mothers before getting the education is sufficient, then after know that is good. Conclusion: There is an effect of flipchart media on the knowledge of mothers in preventing stunting, where p-value = 0.000 <0.05. Keywords: Stunting, Mother of Toddlers, Knowledge, Flipchart media